The revisited genome of Pseudomonas putida KT2440 enlightens its value as a robust metabolic chassis. (28th April 2016) - Belda, Eugeni; van Heck, Ruben G. A.; José Lopez‐Sanchez, Maria; Cruveiller, Stéphane; Barbe, Valérie; Fraser, Claire; Klenk, Hans‐Peter; Petersen, Jörn; Morgat, Anne; Nikel, Pablo I.; Vallenet, David; Rouy, Zoé; et al.
Summary: By the time the complete genome sequence of the soil bacterium Pseudomonas putida KT2440 was published in 2002 (Nelson et al ., 2002 ) this bacterium was considered a potential agent for environmental bioremediation of industrial waste and a good colonizer of the rhizosphere. However, neither the annotation tools available at that time nor the scarcely available omics data—let alone metabolic modeling and other nowadays common systems biology approaches—allowed them to anticipate the astonishing capacities that are encoded in the genetic complement of this unique microorganism. In this work we have adopted a suite of state‐of‐the‐art genomic analysis tools to revisit the functional and metabolic information encoded in the chromosomal sequence of strain KT2440. We identified 242 new protein‐coding genes and re‐annotated the functions of 1548 genes, which are linked to almost 4900 PubMed references. Catabolic pathways for 92 compounds (carbon, nitrogen and phosphorus sources) that could not be accommodated by the previously constructed metabolic models were also predicted. The resulting examination not only accounts for some of the known stress tolerance traits known in P. putida but also recognizes the capacity of this bacterium to perform difficult redox reactions, thereby multiplying its value as a platform microorganism for industrial biotechnology.